Analisis Identitas Visual Kembara Angkasa Sebagai Livery Spesial Ulang Tahun ke 74 Maskapai Garuda Indonesia - Putu Raka Setya Putra; Chris Chalik (LPPM STIKI Malang, 2024)
Airline livery is basically an image in the form of patterns, logos, images and colors used by airlines on part or all of the surface of airline aircraft. the word 'livery' which originally meant uniforms worn by certain officers, is now widely applied, such as in the world of racing and also in the world of transportation, such as on land, sea and air, which is often referred to as airline livery. A country's airline is sometimes the penetration point of a country's tourism campaign, so it is not unusual for many similarities and synergies to emerge between a country's tourism campaign and its airline. Airline livery as a visual identity is not only about aesthetics, but also about broader ideas. Airline livery is not just a brand or style, but also a representation of the values that want to be conveyed through graphic media. This research was conducted to analyze whether garuda indonesia's special livery with the theme of kembara angkasa meets the criteria of visual identity principles that are ideally designed theoretically in its design. this research uses a qualitative descriptive method. The results of this study indicate that garuda indonesia's 74th anniversary special livery with the theme of kembara angkasa has met the criteria of the ideal visual identity principles theoretically, so that the ideally designed visual identity is able to convey the values it represents through visual media.